FASIES DAN KARAKTERISTIK FISIK SEDIMEN KUARTER BERPOTENSI LIKUIFAKSI DI PESISIR KOTA PADANG DAN SEKITARNYA, PROVINSI SUMATRA BARAT - IQBAL, PRAHARA
Geological hazards especially liquefaction is something that can happen and can cause damage to the infrastructure. One of the mitigation measures in relation to the danger of liquefaction is the study of facies and physical characteristics of Quaternary sediments in the coastal city of Padang, West Sumatra Province with the purpose to get the relationship between facies and physical characteristics of the Quaternary sediments liquefaction potential. The method which used in this study are core and CPTu patterns observations to determine which facies developed, laboratory analysis and liquefaction potential analysis to determine the physical characteristics of each facies, and overlay method with Padang September 30, 2009 earthquake liquefaction affected maps for the comparison. Based on lithological associations, CPTu pattern observations, laboratory analysis, and liquefaction potential analysis, there are three facies that develop in research areas with different liquefaction potential. Fluvial sand facies composed by medium sand to very fine sand and without the presence of marine fauna. Types of sediment that developed in fluvial sand facies is GW, SP, and SM with FC ranging from 7-37 %. Fluvial sand facies has cressentic, symmetrical, and fining upward CPTu patterns with the value of Qc 1-20 MPa. This facies has N-SPT ranged from 2-15. Meanwhile, beach ridge sand facies composed by very coarse sand to very fine sand and containing marine fauna. Types of sedimentary that developed in the beach ridge sand facies is more varied than fluvial sand facies, namely GW, SP, SW, and SM with FC ranging from 0.1 to 36 %. This facies has coarsening upward CPTu pattern with the value of Qc 2-25 MPa. Beach ridge sand facies has N-SPT greater than fluvial sand facies, ranging from 4-25. In contrast to the above facies, marsh clay facies composed by clay and containing marine fauna. Types of sedimentary facies developed in marsh clay facies is OH with FC ranging from 65-85 %. Marsh clay facies has cylindrical CPTu pattern with the Qc values from 0.5-4.5 MPa, and has N-SPT ranged from 0-12. In general, liquefaction potential fluvial sand facies is greater than beach ridge sand facies and marsh clay facies, while marsh clay facies has smallest liquefaction potential among two facies